A retrospective comparison of active surveillance to stereotactic radiosurgery for the management of elderly patients with an incidental meningioma - Hallak, Hana; Mantziaris, Georgios; Pikis, Stylianos; Islim, Abdurrahman I; Peker, Selcuk; Samanci, Yavuz; Nabeel, Ahmed M; Reda, Wael A; Tawadros, Sameh R; El-Shehaby, Amr M N; Abdelkarim, Khaled; Emad, Reem M; et al. (Acta neurochirurgica, 2025)
INTRODUCTION: Management for elderly patients (> 65yo) with incidental meningiomas remains unclear. This study aims to characterize the functional and tumor outcomes of expectant and stereotactic radiosurgery (SRS) management of asymptomatic meningioma elderly patients. METHODS: Using retrospectively collected data from 14 centers, SRS outcomes were compared to radiographic and clinical observation of asymptomatic meningiomas in elderly patients following propensity score matching. RESULTS: Following propensity score matching, 114 patients were in each cohort. Tumor control was achieved at 97.37% in the SRS cohort, and no meningioma growth was seen 71.93% of the observation cohorts (p < 0.01; OR 14.44 [95% CI 4.27-48.78]). New neurological deficits developed in 1.39% of the SRS cohort but in none of the patients managed conservatively. 3.5% of patients underwent resection in the active surveillance matched cohort compared to 0.9% of patients in the SRS cohort (p = 0.063; OR 0.135 [95% CI 0.163-1.117]). The all-cause mortality rate was almost half in the SRS group (9.65%) compared to the observation group (18.42%) (p = 0.06; OR 0.47 [95% CI .22-1.03]). CONCLUSION: SRS achieves superior radiological tumor control compared to surveillance but with a slightly increased the risk of new SRS-related neurological deficits in elderly patients with asymptomatic meningiomas. Although SRS reduces meningioma progression, the need for of an open neurosurgical procedure and mortality were not significantly reduced. Furthermore, mortality in the observation group was not directly related to the meningioma in any of the patients.
Keywords: Watchful Waiting; tendenční skóre; Female; výsledek terapie; ženské pohlaví; Meningeal Neoplasms; pozorné vyčkávání; lidé; Meningioma; meningeální nádory; Aged, 80 and over; Treatment Outcome; radiochirurgie; retrospektivní studie; Radiosurgery; Male; Aged; meningeom; Incidental Findings; senioři nad 80 let; senioři; mužské pohlaví; Retrospective Studies; náhodný nález; Propensity Score; Humans